Beberapa Masalah Kewilayahan di Dalam Masyarakat Bali Kuna - I Gusti Made Suarbhawa (Berkala Arkeologi, 1994)
Balinese inscriptions of the X-XIV centuries contain various cases emerged as a social phenomenon. These cases can be observed with the background of people dissatisfaction and various real life experiences. Based on observations of several Balinese inscriptions, it is evident that territorial problems occured in the life of the Ancient Balinese people. This article will examine territorial problems involving social groups. The term of social groups in this article refer to social groups that are mentioned in the inscription such as anak banwa (anak wanwa), anak thani, and karaman who live in the unity of the banwa (wanwa) region of deÇa and thani.